Murine Factor H Co-Produced in Yeast With Protein Disulfide Isomerase Ameliorated C3 Dysregulation in Factor H-Deficient Mice - Kerr, Heather; Herbert, Andrew P.; Makou, Elisavet; Abramczyk, Dariusz; Malik, Talat H.; Lomax-Browne, Hannah; Yang, Yi; Pappworth, Isabel Y.; Denton, Harriet; Richards, Anna; Marchbank, Kevin J.; Pickering, Matthew C.; et al. (Frontiers in Immunology, 2021)
Recombinant human factor H (hFH) has potential for treating diseases linked to aberrant complement regulation including C3 glomerulopathy (C3G) and dry age-related macular degeneration. Murine FH (mFH), produced in the same host, is useful for pre-clinical investigations in mouse models of disease. An abundance of FH in plasma suggests high doses, and hence microbial production, will be needed. Previously, Pichia pastoris produced useful but modest quantities of hFH. Herein, a similar strategy yielded miniscule quantities of mFH. Since FH has 40 disulfide bonds, we created a P. pastoris strain containing a methanol-inducible codon-modified gene for protein-disulfide isomerase (PDI) and transformed this with codon-modified DNA encoding mFH under the same promoter. What had been barely detectable yields of mFH became multiple 10s of mg/L. Our PDI-overexpressing strain also boosted hFH overproduction, by about tenfold. These enhancements exceeded PDI-related production gains reported for other proteins, all of which contain fewer disulfide-stabilized domains. We optimized fermentation conditions, purified recombinant mFH, enzymatically trimmed down its (non-human) N-glycans, characterised its functions in vitro and administered it to mice. In FH-knockout mice, our de-glycosylated recombinant mFH had a shorter half-life and induced more anti-mFH antibodies than mouse serum-derived, natively glycosylated, mFH. Even sequential daily injections of recombinant mFH failed to restore wild-type levels of FH and C3 in mouse plasma beyond 24 hours after the first injection. Nevertheless, mFH functionality appeared to persist in the glomerular basement membrane because C3-fragment deposition here, a hallmark of C3G, remained significantly reduced throughout and beyond the ten-day dosing regimen.